Experimental status of 7Be production and destruction at astrophysical relevant energies. Issue 1 (January 2016) - Leva, A Di; Gialanella, L; Strieder, F
Abstract: The production and destruction of 7 Be plays a significant role in the Big Bang Nucleosynthesis as well as in the framework of the solar neutrino. The 3 He(α, γ) 7 Be reaction cross sections has been measured several times in the last decades, but the precision achieved on reaction rate determinations at the relevant astrophysical energies is not yet satisfactory. The experimental status of this reaction will be critically reviewed, and the theoretical descriptions available will be discussed.